Three technologies for automated trading - Debenham, John (2006)
Three core technologies are needed for automated trading: data mining, intelligent trading agents and virtual institutions in which informed trading agents can trade securely both with each other and with human agents in a natural way. This paper describes a demonstrable prototype that integrates these three technologies and is available on theWorldWideWeb. This is part of a larger project that aims to make informed automated trading a reality.